Self-Regulated Learning is the Internalization of Mobile Seamless Learning-Based Learning Strategies in Improving Communication Skills - Zutiasari, Ika; Heri, Heri; Rahayu, Wening Patmi; Rusmana, Dede (PT FORMOSA CENDEKIA GLOBAL, 2024)
The utilization of technology in the teaching and learning process is a new innovation challenge for lecturers to be able to improve student understanding of the material. The application of mobile seamless learning through self-regulated learning for business communication courses is a profitable opportunity to improve the communication skills of Business Education study program students. This research method is Research and Development with PLOMP model. The application of Edubis can improve students' oral and written communication skills. There has been an increase of 11% from before using the application to using the application so that the Edubis Application can become an effective learning media platform for students. Novelty: Only a few research studies discuss self-regulated learning through digital learning based on mobile seamless learning. Self-regulated learning is independent learning, which refers to learning driven by students' thoughts and behavior toward their learning goals.